Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Pegawai ASN dan Non-ASN Pada Era New Normal di Kantor Kecamatan Tanah Abang Kabupaten Penukal abab Lematang Ilir (PALI) - Dita Novalia; Sabeli Aliya (Universitas Batanghari, 2022)
This study aims to determine how thein fluence of the work environment and apediscip line on the performance of ASN and Non ASN Employee sinthe New Normal Eraat the Tanah Abang District Office, Penukal Abab Lematang Ilir (Pali) Regency. There search method used in this study is aquantitative method with data collection us ingquestion nairesto test the hypotheses that have been set. The population in this study was all civil servant sandnon-as an employees at the Tanah Abang sub-district office (PALI), which am ounted to 40 employee sand all of them were used as sample sinthis study. The result sobtained in this study, partially the work environment variable has no significant effect on employee performance, partially the work discipline variable has asignificant influence on employee performance and simultane ously the work environment variable and work discipline has appositive influence on employee performance.